CHALLENGES AND OPPORTUNITIES OF PRIVATE UNIVERSITIES IN FACING THE DIGITAL ERA IN KENDARI: A DESCRIPTIVE STUDY - Kirana, Candra; Mokodompit, Eliyanti Agus (Management Studies and Business Journal (PRODUCTIVITY), 2024)
With the rapid development of digital technology, higher education institutions worldwide face challenges in integrating technology into the educational process. However, private universities in Kendari still encounter various barriers in optimally utilizing digital technology. This study identifies the knowledge gap regarding the application of digital technology in higher education, particularly at private universities in Kendari, which are constrained by inadequate infrastructure and limited digital skills among faculty and students. This research used a descriptive qualitative research design, with in-depth interviews conducted with five informants who are experts in education and technology. The findings show that, despite significant challenges, digital technology offers great opportunities to expand access and improve the quality of education, especially through e-learning platforms and online learning. The implications of this study provide practical insights for private university managers to develop more effective technology strategies to enhance educational quality and the utilization of technology in the future.